Role of atrial high-rate episodes in stratifying thromboembolic risk: a multiple cut-off diagnostic meta-analysis - Saglietto, Andrea; Ballatore, Andrea; Griffith Brookles, Carola; Xhakupi, Henri; De Ferrari, Gaetano Maria; Anselmino, Matteo (Frontiers in Cardiovascular Medicine, 2023)
Aims: Despite the high prevalence of atrial high-rate episodes (AHRE) detected by cardiac implantable electronic devices (CIED), clinical guidelines and consensus documents have failed to agree on a universal AHRE definition and on a temporal cut-off related to subsequent thromboembolic events. The present is a diagnostic test accuracy meta-analysis aiming to derive from available literature the optimal temporal threshold of clinically significant AHRE.Methods: PubMed/MEDLINE and EMBASE databases were screened for studies on CIED patients reporting incidence of thromboembolic events referred to at least one AHRE temporal cut-off. 23 studies were included: 19 considering the longest single AHRE and 4 the AHRE burden, respectively. A random-effect diagnostic test accuracy meta-analysis with multiple cut-offs was performed. Two analyses, according to AHRE temporal cut-off subtype (longest episode vs. cumulative burden), were performed.The analysis on the longest single AHRE indicated 0.07 minutes as the optimal duration to differentiate AHRE associated or not to thromboembolic events [sensitivity 65.4% (95% CI 48.8-79.0%), specificity 52.7% (95%CI 46.0-59.4%), area under the summary receiver operating characteristic curve (AUC-SROC): 0.62]. The analysis on AHRE burden indicated 1.4 minutes as the optimal cut-off [sensitivity 58.2% (95%CI 25.6-85.0%), specificity 57.5% (95% CI 42.0-71.7%), AUC-SROC 0.60]. A sensitivity analysis excluding patients with history of AF, and including high-quality studies only yielded similar results.The presence of AHRE, rather than a specific duration, relates to an increased, albeit low, thromboembolic risk in CIED patients. Any AHRE should constitute an additional element in patient-specific thromboembolic risk assessment.